2013
DOI: 10.1177/2156869313491273
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Meaning-making after Spousal Loss on Trajectories of Psychological Distress

Abstract: Stress process researchers note that people actively seek to alter the impact of stressful life events through various coping mechanisms. Spousal bereavement sometimes requires individuals to revise their assumptions about the world and themselves. Meaning-making, comprising the dual processes of searching for and finding meaning, may be employed to alleviate symptoms of grief following spousal bereavement. The current study uses multilevel modeling to examine the influence of searching for and finding meaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It is possible that immediately following the death of a spouse, the surviving partner best copes by relying on their own memories to find comfort, possibly minimizing the immediate impact of social relationships on one’s mental health. Further, this might be more apparent among widowed older adults due to having been married longer, hence having more shared memories (Brown et al, 2004; Carr, 2020; Young & Foy, 2013). In addition, compared to young or middle-aged widowed individuals, older adults are more likely to have smaller social circles, requiring reliance on personal coping through grief (Szabo et al, 2020; Vos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that immediately following the death of a spouse, the surviving partner best copes by relying on their own memories to find comfort, possibly minimizing the immediate impact of social relationships on one’s mental health. Further, this might be more apparent among widowed older adults due to having been married longer, hence having more shared memories (Brown et al, 2004; Carr, 2020; Young & Foy, 2013). In addition, compared to young or middle-aged widowed individuals, older adults are more likely to have smaller social circles, requiring reliance on personal coping through grief (Szabo et al, 2020; Vos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that examined different aspects of spirituality have found that meaning is an important aspect of effective management of general psychological distress [39] in both bereaved caregivers [39][40][41] and cancer survivors [31,33]. In one prospective study, mothers who reported finding meaning in life through the caregiving experience reported lower distress as they navigated bereavement, further indicating that cognitively processing the impact of a stressful experience can be a protective factor against future distress [42].…”
Section: Predictors Of Bereavement-specific and General Distressmentioning
confidence: 98%
“…Meaning making does not necessarily lead to meaning made (e.g. Davis et al 2000;Young & Foy 2013). In particular, few studies have found an association between PTG and the core belief system (Park & Fenster 2004).…”
Section: The Independence Model: Meaning Discrepancy + Ptg → Anxiety/mentioning
confidence: 99%
“…Davis et al . ; Young & Foy ). In particular, few studies have found an association between PTG and the core belief system (Park & Fenster ).…”
Section: Introductionmentioning
confidence: 99%